In Silico and In Vitro Analysis of Sulforaphane Anti-Candida Activity - Bruna L. R. Silva; Gisele Simão; Carmem D. L. Campos; Cinara R. A. V. Monteiro; Laryssa R. Bueno; Gabriel B. Ortis; Saulo J. F. Mendes; Israel Viegas Moreira; Daniele Maria-Ferreira; Eduardo M. Sousa; Flávia C. B. Vidal; Cristina de Andrade Monteiro; et al. (MDPI AG, 2022)
Oropharyngeal candidiasis/candidosis is a common and recurrent opportunistic fungal infection. Fluconazole (FLZ), one of the most used and effective antifungal agents, has been associated with a rise of resistant Candida species in immunocompromised patients undergoing prophylactic therapy. Sulforaphane (SFN), a compound from cruciferous vegetables, is an antimicrobial with yet controversial activities and mechanisms on fungi. Herein, the in silico and antifungal activities of SFN against C. albicans were investigated. In silico analyzes for the prediction of the biological activities and oral bioavailability of SFN, its possible toxicity and pharmacokinetic parameters, as well as the estimates of its gastrointestinal absorption, permeability to the blood-brain barrier and skin, and similarities to drugs, were performed by using different software. SFN in vitro anti-Candida activities alone and in combination with fluconazole (FLZ) were determined by the broth microdilution method and the checkerboard, biofilm and hyphae formation tests. Amongst the identified probable biological activities of SFN, nine indicated an antimicrobial potential. SFN was predicted to be highly absorbable by the gastrointestinal tract, to present good oral availability, and not to be irritant and/or hepatotoxic. SFN presented antifungal activity against C. albicans and prevented both biofilm and hyphae formation by this microorganism. SFN was additive/synergistic to FLZ. Overall, the data highlights the anti-Candida activity of SFN and its potential to be used as an adjuvant therapy to FLZ in clinical settings.